Многопараметрические гибридные схемы виртуального разделения каналов в интегральных сотовых сетях связи. II - Меликов, А.З.; Пономаренко, Л.А.; Велиджанова, Г.М. (Управляющие системы и машины, 2016)
Предложена многопараметрическая схема виртуального разделения общего пула каналов в интегральной сотовой сети связи, в которой обрабатываются новые и хэндовер-вызовы данных и речи. Выделены две индивидуальные зоны каналов для вызовов данных и речи и общая зона для их совместного использования. Даны два варианта доступа разнотипных вызовов в общую зону. Запропоновано багатопараметричну схему віртуального розподілу загального пулу каналів в інтегральній стільниковій мережі зв’язку, де обробляються нові та хендовер-виклики даних і мови. Виокремлено дві індивідуальні зони для викликів даних і мови та загальна зона для спільного їх використання. Подано два варіанти доступу різнотипних викликів у загальну зону. Introduction. In Integrated Cellular Network (ICN) four type of calls are distinguished: handover voice calls (hv-calls), new voice calls (ov-calls), handover data calls (hd-calls) and new data calls (od-calls). The indicated calls have the different quality of service (QoS) requirements. To satisfy these requirements in the available literature the several channels partition schemas are proposed. Purpose. New two schemas to common channels partition in Integrated Cellular Network (ICN) are presented. The indicated schemas allow to satisfy the different requirement of heterogeneous calls to quality of service (QoS) metrics. Both schemas are based on the idea of Virtual Partition with Common Zone (VPwCZ). Virtual partition means the following: on termination of v-call processing the released channel which is in a v-zone, is transferred in a vd-zone at presence of v-call, and the channel in a vd-zone, carrying out v-call processing, fixed to a v-zone. In both schemas in individual zone the guard channels scheme for handover calls are used. In one of them (VPwCZv2) the common zone of channels are used by Complete Sharing (CS) scheme; in another scheme (VPwCZv2) in common zone of channels the cutoff scheme is used. The problem develops the effective methods to calculate the QoS metrics of heterogeneous calls. Method. The functioning of the investigated model is described by two-dimensional Markov Chain (2-D MC). Infinitesimal matrix of appropriate 2-D MC in both schemas are developed. It is shown that the stationary distribution of an indicated 2-D MC in both cases have the multiplicative form and the explicit formulas are developed. The algorithms to calculate QoS metrics of the different call types are proposed. Results. The results of the numerical experiments for both schemas of channels partitions are demonstrated. In order to be accurate, only the dependencies of QoS metrics on parameters of channels partition schemas are shown. These results allow to perform detailed analysis of behavior of QoS metrics in wide area of the models with changing parameters. Conclusion. The simple algorithms to calculate QoS metrics in ICN are developed. Complexities of the algorithms are very low and they allow to select the optimal partition scheme in the investigated networks.